Hodgkin's disease presenting as liver abscesses. Issue 8 (August 1991) - Zaman, A; Bramley, P N; Wyatt, J; Simmons, A; Losowsky, M S; Bolton, R
Abstract : A patient is reported who presented with sterile hepatic abscesses which proved to be the first manifestation of Hodgkin's disease. He failed to improve with antibiotic treatment but responded to combined chemotherapy. Liver involvement as the first sign of Hodgkin's disease is rare. Liver abscesses due to Hodgkin's disease seem to be previously unreported.